Autophagy, cancer stem cells and drug resistance. Issue 5 (4th February 2019) - Smith, Alexandra G; Macleod, Kay F
Abstract: Autophagy is a cellular survival mechanism that is induced by cancer therapy, among other stresses, and frequently contributes to cancer cell survival during long periods of dormancy and the eventual outgrowth of metastatic disease. Autophagy degrades large cellular structures that, once broken down, contribute to cellular survival through the recycling of their constituent metabolites. However, the extent to which this fuel function of autophagy is key to its role in promoting stemness, dormancy and drug resistance remains to be determined. Other roles for autophagy in determining cell fate more directly through targeted degradation of key transcription factors, such as p53 and FoxO3A, or by enforcing a reversible quiescent growth arrest, are discussed in this review. This review also highlights the need to parse out the roles of different forms of selective autophagy in stemness, CD44 expression and dormancy that, for example, are increasingly being attributed explicitly to mitophagy. The clinical relevance of this work and how an increased understanding of functions of autophagy in stemness, dormancy and drug resistance could be manipulated for increased therapeutic benefit, including eliminating minimal residual disease and preventing metastasis, are discussed. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.